PERAN PERSEPSI NILAI DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN ELEKTRONIK TERHADAP KEPUASAN KONSUMEN - Putra, Anak Agung Angga Andika; Widagda K, I Gst. Ngurah Jaya Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The development of technology and information has created changes to buying and selling transaction activities in the payment system mechanism that uses electronic payment instruments. Go-Pay is an electronic payment method provided and contained in the Go-Jek application feature in order to facilitate transactions. The purpose of this study was to explain the role of perceived value in mediating the effect of electronic service quality on consumer satisfaction. This research was conducted in Denpasar City. Samples were taken as many as 180 respondents through purposive sampling method and distributed using a google form questionnaire with adjusted criteria. Measured by 36 indicators and using a 5-point Likert scale. The data analysis technique used is path analysis, Sobel test and VAF test. The results of this study indicate that all hypotheses are accepted. The quality of electronic services has a positive and significant influence on customer satisfaction. The quality of electronic services has a positive and significant effect on perceived value. Perceived value has a positive and significant influence on consumer satisfaction. Perceived value plays a significant role in mediating the effect of electronic service quality on consumer satisfaction.